A study of fancy dress masquerade costumes in Winneba, Ghana (1958-2020) - Dennis, Albert (University of Cape Coast, 2021)
The careful representation of Fancy Dress masquerades in the Ghanaian space, especially in Winneba, has been held in high esteem over the decades as part of Ghana’s popular culture. Undoubtedly, the use of costume in this performative art serves as the pillar on which masquerading hinges. Although Fancy Dress masquerade costumes contribute greatly to the success of the performance, there appears to be little or no empirical study on the use of costumes in this performative art in Winneba. This study sought to explore and document the use of Fancy Dress masquerade costumes among four masquerade clubs in Winneba from 1958 to 2020. Using the qualitative approach and multiple instruments (semi-structured interviews, observation and document study) to collect data, thematic and document analytical frames were used to analyse the data. Anchored on Goffman’s (1959) Impression Management Theory, the findings revealed that the designing of Fancy Dress masquerade costumes is based on the diverse inspirations of the various clubs with the use of varying materials and the costumes characterised by various forms of aesthetics and significance. Ultimately, the study contributes to scholarship on the use of costumes for masquerade performances. With a treasure trove of findings, I recommend a study be conducted on Fancy Dress masquerade costumes in other Regions in Ghana to add to the discourse on Fancy Dress masquerade costumes.
xvii, 307p:, ill
Keywords: Aesthetics Fancy Dress masquerade costumes Masquerader Materials Performance